(untitled) (Alternautas, 2024)
Our proposal for this special issue was inspired by the breadth of commemorations we were witnessing in the lead-up to September 11th, 2023, the 50th anniversary of the military coup that has cast a shadow over Chileans until today. Seeking to avoid repeating the question of where, how, and between whom European-Latin American solidarity takes and has taken place from its inception, we intended this special issue to go beyond the question of chronological memory and historiography to rethink the cyclical and reiterative nature of these solidarities rooted in the Cold War. From the unique vantage point of living with the third generation of Chile’s exile diaspora, we wanted to revisit the current-day vernaculars and practices of European-Latin American relations through concepts of translocal and transgenerational solidarity. Similarly, at a time when older categories of internationalism and anti-imperialism have taken on entirely new meanings for protest movements and social justice activism, adapted definitions of the vocabulary surrounding human rights, solidarity, and democracy play an increasingly central role in activism narratives and need to be more thoroughly scrutinised.